Transform-Data-by-Example (TDE): Extensible Data Transformation in Excel - He, Yeye; Ganjam, Kris; Lee, Kukjin; Wang, Yue; Narasayya, Vivek; Chaudhuri, Surajit; Wang, Yue (International Conference on Management of Data (SIGMOD), 2018)
Business analysts and data scientists today increasingly need to clean, standardize and transform diverse data sets, such as name, address, date time, phone number, etc., before they can perform analysis. These ad-hoc transformation problems are typically solved by one-off scripts, which is both difficult and time-consuming. Our observation is that these domain-specific transformation problems have long been solved by developers with code libraries, which are often shared in places like GitHub. We thus develop an extensible data transformation system called Transform-Data-byExample (TDE) that can leverage rich transformation logic in source code, DLLs, web services and mapping tables, so that end-users only need to provide a few (typically 3) input/output examples, and TDE can synthesize desired programs using relevant transformation logic from these sources. The beta version of TDE was released in Office Store for Excel.